2016
DOI: 10.1177/1090198115606919
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Control in a Clinic-Based Sample of Diabetics in M’Bour Senegal

Abstract: We found that glycemic control in our sample was suboptimal. Length of time with diabetes was one of the key factors related to glycemic control. Length of time with diabetes is negatively associated with glycemic control. Early diagnosis and early glycemic control are essential to long-term glycemic control screening, and early detection for diabetes is uncommon given the general lack of health insurance and most people paying out of pocket for medical care. In the absence of universal health insurance, publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…This finding compared favourably with that of Titty (23) in Tamale (40%), Chinenye, Uloko (24) in Nigeria (32.4%) and Musenge, Manankov (25) in Zambia (38.7%). However the rate of poor glycaemic control recorded in this study is higher than that reported by Kamuhabwa and Charles (26) in Tanzania (23.9%) and BeLue, Ndiaye (27) in Senegal (24.8%).…”
Section: Discussioncontrasting
confidence: 78%
“…This finding compared favourably with that of Titty (23) in Tamale (40%), Chinenye, Uloko (24) in Nigeria (32.4%) and Musenge, Manankov (25) in Zambia (38.7%). However the rate of poor glycaemic control recorded in this study is higher than that reported by Kamuhabwa and Charles (26) in Tanzania (23.9%) and BeLue, Ndiaye (27) in Senegal (24.8%).…”
Section: Discussioncontrasting
confidence: 78%
“…Moreover, two surveys in Nigeria [ 48 , 49 ] have shown that the economic burden of diabetes is high for some patients due to the impact of out of pocket payments. In countries like Rwanda [ 19 , 50 , 51 ], Ethiopia [ 25 , 26 ], Swaziland [ 25 ], Kenya [ 52 ], Nigeria [ 53 ] Burundi, Senegal [ 54 ], and the Democratic Republic of Congo [ 51 ] diabetes drugs are still unavailable or are too expensive to be accessible. This is identified by patients as one of the biggest reasons for nonadherence to treatment [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this systematic review had some limitations, as mentioned by their authors. These limitations include low number of participants [ 28 , 43 , 63 , 65 – 67 , 73 ], participants and centers not representative sample of the studied country [ 25 , 29 , 40 , 45 , 53 , 54 ]. Other studies reported high loss to follow-up [ 27 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different rates of poor glycemic control were reported in the various African settings e.g. 74.0% in Cameroon and Guinea [ 15 ], 61.3% in Zambia [ 17 ], 69.7% in Tanzania [ 18 ], 75.2% in Senegal [ 16 ], 79.2% in Uganda [ 19 ], and 62% in Nigeria [ 20 ].…”
Section: Discussionmentioning
confidence: 99%